How to be a great boss - Wickman, Gino; Boer, René (Findaway World, 2016)
If your employees brought their "A-Game" to work every day, what would it mean for your company's performance? Studies have repeatedly shown that the majority of employees are disengaged at work. But it doesn't have to be this way. Often, the difference between a group of indifferent employees and a fully engaged team comes down to one simple thing?a great boss. In How to Be a Great Boss, Gino Wickman and Ren? Boer present a straightforward, practical approach to help bosses at all levels of an organization get the most from their people. They share time-tested tools that have worked for more than 30,000 bosses in every industry. You can learn to be a great boss?and dramatically improve both your organization's performance and your team's excitement about their work